The Effect of Using‏‏Technology-Enhanced English Course (TEEC) in‏‏Teaching English as ‎a‏‏Foreign‏‏Language at Preparatory Schools - Madhloom Hashim ALI, Nadhim (International Journal of Psychosocial Rehabilitation, 2025)
This study aims to explore the impact of the Technology-Enhanced English Course (TEEC) in teaching English as a foreign language at Iraqi preparatory schools. The TEEC is a notable trend that integrates learning and teaching by combining traditional teaching methods with authentic materials. Teachers are consistently enabled to modify their teaching methods through the use of technology, which enables students to assume responsibility for learning in the target language. The sample was randomly selected and consisted of 44 enrolled English teachers to collect the necessary information. The findings showed that the majority of diverse teachers highlighted the significance of technology based on active learning in the classroom teaching of English as a foreign language. Implementing fresh information to enhance student engagement in the target language. The difference between traditional teaching and the technology-enhanced course was therefore significant at the p